Studying the Principles and Ordinances of Transactions of Another Person’s Property in Imamayeh Fiqh, the Law of Iran and the Law of England - Hamed Khubyari; Sayyed Muhammad Sadiq Tabatabaei; Ali Reza Arashpour (آموزه‌‌های فقه مدني)
Most law scholars and well-known Islamic jurists consider that the fudhuli (unauthorized) regulations are of the the general rules of the agreements (contracts) and have generalized (spread) it to all types of the contracts. This broadness causes that some law scholars think that some fudhuli (unauthorized) rulings is in conflict with the public order. In contrast in the law of England as an excuse to maintain public order there are exceptions to the rule “the impossibility of transferring of title by the unauthorized person (a person has no ownership right)” and in some case the transfer of another person’s property is effective. Moreover, in the law of this country to facilitate the business affairs, the transaction of the agent acting without or outside his authority or the transaction of any person who pretends (claims) as an agent are effective. The disagreement between attitudes about efficiency of the legislation about the transfer of another person’s property originates from the difference of basics of “the transaction (sale) of another person’s property” in these two legal systems. In this paper with differentiating between the fudhuli (unauthorized) transactions of “mora’a” (meaning in the sale there is a right for the third person and the efficiency of the transaction relating to fulfil his right) and “moquf” (meaning ite efficiency relates to the consent of the true owner), it will be revealed that ineffectiveness of the recent transactions has been the theory “assigning the contract of sale to the true owner” and in the law of England the transaction of another person’s property is established in proportion to the ruling pursuant to the basics “agency resulting from ratification” and the Contract management (It’s a term which is used in the law of Iran and not explicitly in the law of England meaning: Contracting in situation that it does not conform to the accepted criteria (rules) by the legislature but the legislature for different social reasons is not going to announce its annulment).